Finance and Development, December 2000. (Finance and Development; Finance and Development ;, 2000)
This paper describes the need to broaden the agenda for poverty reduction. The broadening of the agenda follows from a growing understanding that poverty is more than low income, a lack of education, and poor health. The poor are frequently powerless to influence the social and economic factors that determine their well being. The paper highlights that a broader definition of poverty requires a broader set of actions to fight it and increases the challenge of measuring poverty and comparing achievement across countries and over time.